Legal Policy in the field of social protection of children in the Republic of Kazakhstan - Yessekeyeva , А.А.; Оteuova , А.; Kuanaliyeva, Г.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The article is devoted to the problem of legal policy in the field of social protection of children in the Republic of Kazakhstan. The purpose of the article is a theoretical justification of the right to social protection of children, as well as a comprehensive analysis of legal policy in the field of social protection of children. This scientific article examines the issues of the state's legal policy in the field of protection of children's rights in the Republic of Kazakhstan. The study analyzes the essence and content of the concept of «social protection». Concrete steps are being taken in the Russian and Turkish states to implement State policies in the field of protecting children's rights and ensuring their safety. With the implementation of the adopted strategic documents, it also becomes clear what positive factors the States are seeking. The authors adhere to the principle of the transition of research work from the general to the particular. The authors, conducting a comparative analysis of the state policy of the Russian and Turkish states regarding the rights of the child, prove the need to develop a strategic document and an action plan on the rights of the child for the long term in the country, and also reveal the principles on which the plan will be based.